2021
DOI: 10.1111/and.14202
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐loaded cyclodextrin attenuates dilution effect and improves quality of bovine low sperm insemination doses during cryopreservation

Abstract: Semen cryopreservation plays a vital role in the success of artificial insemination (AI), which is the mostly applied technology for the production and genetic improvement of bovine (Lone et al., 2019;Vishwanath & Shannon, 2000). Although the quality of cryopreserved semen has enhanced during the past several decades, around 50% of the spermatozoa are damaged during the freeze-thaw process, leading to reduced freezability and capacity to fertilise (Layek et al., 2016), which is responsible for the limited gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Each qualifying ejaculate was split to 4 aliquots and diluted with egg yolk tris glycerol (EYTG) extender up to 20, 15, 10 and 5 million spermatozoa/0.25 ml, respectively. This was followed by packing aliquots into straws (0.25 ml), equilibrated at 4°C for 4 h, and cryopreserved in liquid nitrogen (Lone et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each qualifying ejaculate was split to 4 aliquots and diluted with egg yolk tris glycerol (EYTG) extender up to 20, 15, 10 and 5 million spermatozoa/0.25 ml, respectively. This was followed by packing aliquots into straws (0.25 ml), equilibrated at 4°C for 4 h, and cryopreserved in liquid nitrogen (Lone et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In order to make extensive use of sex‐sorted semen in dairying and to ensure maximum distribution of elite semen, small sperm doses are packed in the straws followed by their cryopreservation (Ballester et al, 2007; Mohanty et al, 2018). Few studies revealed that the frozen–thawed sperm quality gets compromised at higher dilutions in terms of individual motility (Karan et al, 2018), live sperm count (Garner et al, 1997), membrane intactness (Lone et al, 2021) and acrosomal integrity (Karan et al, 2018; Lone, Mohanty, Bhakat, Paray, Baithalu, et al, 2020). How the different sperm motion and functional attributes are affected by extensive semen dilution remains to be elucidated, so the present study was aimed to evaluate the effect of dilution of bull semen from 20 million to 5 million (M), sperm dose per straw on post‐thaw sperm motion characteristics (total motility [TM], progressive motility [PM], rapid motility [RM], slow motility [SM], average path velocity [VAP], straight linear velocity [VSL], curvilinear velocity [VCL], amplitude of lateral head displacement [ALH], beat cross frequency [BCF], straightness [STR] and linearity [LIN]), and sperm function attributes (live spermatozoa, moribund spermatozoa, dead spermatozoa, live acrosome intact [LAI] spermatozoa, live acrosome reacted [LAR] spermatozoa, dead acrosome intact [DAI] spermatozoa, dead acrosome reacted [DAR] spermatozoa, hypo‐osmotic swelling test [HOST], protamine deficiency, non‐capacitated [NC] spermatozoa, capacitated spermatozoa, acrosome reacted [AR] spermatozoa and lipid peroxidation [LPO]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of the sea cucumber extract reported in this study is probably due to the specific composition of the sea cucumber itself. Both polysaccharides [28], saponins [29], polyphenols, and cholesterol [30] have been shown to have a beneficial effect on sperm. The health-promoting properties of sea cucumber result from the content of many biologically active substances [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Both polysaccharides [28], saponins [29], polyphenols, and cholesterol [30] have been shown to have a beneficial effect on sperm. The health-promoting properties of sea cucumber result from the content of many biologically active substances [30,31]. It is known that sea cucumbers are rich in polysaccharides, such as glucosamines, galactose, or glucuronic acid, which have antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%